Cytogenetic analysis of five Hypostomus species (Siluriformes, Loricariidae) - Martinez,Emanuel Ricardo Monteiro (2011)
In this work, we analyzed the karyotypes of five species. Hypostomus cf. heraldoi, from the Mogi-Guaçu River, had 2n = 72 chromosomes, with a nucleolar organizer region (NOR) in one chromosomal pair. Hypostomus regani, from the Mogi-Guaçu River had 2n = 72 chromosomes with NORs in two chromosomal pairs. Hypostomus sp., from the Mogi-Guaçu River basin, had 2n = 68 chromosomes, with NORs in two chromosomal pairs. Hypostomus aff. agna, from Cavalo Stream, had 2n = 74 chromosomes with NORs in two chromosomal pairs. Hypostomus cf. topavae, from Carrapato Stream, had 2n = 80 chromosomes, with NORs in two chromosomal pairs. Hypostomus species showed marked diversity in the karyotypic formula, which suggested the occurrence of several Robertsonian rearrangements and pericentric inversions during the evolutionary history of this genus. This hypothesis was supported by the occurrence of a large number of uniarmed chromosomes and multiple NORs in a terminal position in most species and may be a derived condition in the Loricariidae.